Nitrogen Mineralization Potential Regulated by Hot Water and Ultrasound Pre-Treatment from a Long-Term Paddy Soil - Toan, Nguyen-Sy (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
To investigate the impact of pre-treating on mineralized nitrogen production, we carried out an anaerobic incubation following five pre-treatment sets: (1) 5 g soil/50 ml water (Control), (2) 5 g soil/50 ml water/80℃/ 4 hours (Hot water), (3) 2.5 g soil/50 ml water/80℃/4 hours + 2.5 g soil (Mixed hot water), (4) 5 g soil/ 50 ml water/ultrasound 37 Hz/30 minutes (Ultrasound), and (5) 2.5 g soil/50 ml water/ultrasound 37 Hz/30 minutes + 2.5 g soil (Mixed ultrasound). Inorganic nitrogen was extracted before incubation (Initial In-N) and after 4 weeks of anaerobic incubation (Total Min-N and Net Min-N). The results reveal that Initial In-N ranged from 21.8 to 23.5 mg N/kg and was similar among four pre-treatment methods. Interestingly, Net Min-N was promoted by heating hot water; meanwhile, ultrasound pre-treatment did not enhance soil mineralization potential. This indicates that pre-treating soil with hot water could be a promising method to enhance soil nitrogen mineralization.